Bureaucracies under authoritarian pressure: legal destabilisation, politicisation and bureaucratic subjectivities in contemporary Turkey. Issue 3 (September 2022) - Saglam, Erol
Abstract: Drawing on ethnographic research across two street-level bureaucratic institutions in Istanbul, Turkey in the late 2010s, this paper traces the causes and implications of the politicisation of bureaucrats in the context of authoritarianisation. It argues that politicisation of bureaucrats cannot solely be taken as a reflection of the erosion of bureaucratic autonomy and capacity but must be explored further to reveal how bureaucrats cope with authoritarian pressure as well socio-legal destabilisations to preserve their institutional ethos. To this aim, I demonstrate how bureaucrats get politicised in response to authoritarian policies and, in turn, labour to uphold the rule of law despite politico-legal risks. The paper particularly focuses on how bureaucrats weave political solidarity and circulate anti-government discourses and how they use their knowledge of the legal-regulatory repertoire and archives to deter and 'correct' unlawful practices through their everyday work. The paper generates insights into the fashionings of political subjectivities and agency by bureaucrats through their labouring in the face of authoritarian interventions, legal disruptions and the increasing interactions with the citizenry. In doing this, my objective is to shed light on the everyday workings of authoritarian state and to get a better picture of the way the law is 'made real' (Latour, 2002 ) across mundane encounters between bureaucrats and the citizenry.